(untitled) (Journal of School Administration Research and Development, 2018)
Teachers’ situated knowledge of the classroom and teaching suggests that they can play an important role in promoting and supporting change in teaching practice even if they are not formally designated as leaders. We selected 32 secondary mathemat- ics and science teachers and supported them in enrich- ing their instructional practice and in becoming in- structurally-focused teacher leaders. We describe the qualities we sought in teachers who were to become effective teacher leaders, and we share the ways in which we assessed those characteristics. We explain our rationale, instruments, and interview questions used in the selection of the teacher leaders. After four years, our teachers have served and continue to serve in numerous formal and informal leadership roles. We offer three recommendations to administrators for nurturing teacher leaders.